Genetic diversity of bitter and sweet African bush mango trees (Irvingia spp., Irvingiaceae) in West and Central Africa - MISSIHOUN, ANTOINE ABEL HOUMÈNOU; Vihotogbé, Romaric; SINSIN, AUGUSTIN BRICE (My University, 2015)
Economically important food tree species in sub-Saharan Africa should be domesticated to enhance their production within agro forestry systems. The African bush mango trees (Irvingia species) are highly preserved and integrated in agro forestry systems in tropical Africa. However, the taxonomic debate related to the species or varietal status of the bitter and sweet fruited African bush mango trees hinders their domestication process and rational use. Amplified fragment length polymorphisms (AFLPs) and chloroplast simple sequence repeats (cpSSRs) were used in this study to assess the genetic diversity of African bush mango trees and to test the distinction between bitter and sweet fruited trees, sampled across Togo, Benin, Nigeria and Cameroon. Both the AFLPs and cpSSRs showed low genetic diversity for the Dahomey Gap bitter trees population. This is due to the higher fragmentation and the continuous reduction of this small sized population occurring in a limited forest ecosystem. The higher polymorphism and genetic diversity of the sweet mango tree populations in Benin and Togo showed the effects of domestication of materials of different geographical origin coupled with the frequent long distance transfer of genetic materials. When used separately, the AFLPs and cpSSRs failed to consistently discriminate the populations and type of trees. From the combined dataset, both markers differentiated geographically recognizable groups; bitter from sweet mango trees. However, Nigerian sweet mango trees clustered with the bitter ones. The suitability of AFLPs and cpSSRs to test our hypotheses within Irvingia needs to be thoroughly reassessed.
Keywords: AFLP; Benin; cpSSR; Togo; Dahomey Gap; Irvingia; taxonomy; domestication.